2018
DOI: 10.1007/s10494-018-9959-6
|View full text |Cite
|
Sign up to set email alerts
|

An LES Investigation of the Near-Wake Flow Topology of a Simplified Heavy Vehicle

Abstract: Recent experimental investigations by McArthur et al. (J. Fluids Struct. 66, 293-314, 2016) in the wake of a simplified heavy vehicle or commonly known as the ground transportation system (GTS) model has shown that the flow topology is invariant over a large range of Reynolds numbers [2.7 × 10 4 − 2 × 10 6 ]. Numerical simulations are performed to investigate the initial flow topology at a Reynolds number of 2.7 × 10 4 , using well-resolved large eddy simulations (LES). In the vertical midplane behind the GTS,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 74 publications
(106 reference statements)
8
25
0
Order By: Relevance
“…Simulations which accurately capture the wake unsteadiness at high Reynolds number, and which furthermore extend over the large time scales of bi-modal switching, are very costly. Unsteady simulations of simplified bluff body flows have been performed using partially averaged Navier-Stokes (PANS), simulations (Mirzaei, Krajnović & Basara 2015;Rao et al 2018a), unsteady Reynolds-averaged Navier-Stokes simulations (Khalighi, Chen & Iaccarino 2012), detached eddy simulations and large eddy simulations (Krajnović & Davidson 2003;Serre et al 2013;Aljure et al 2014;Östh et al 2014;Rao et al 2018b), some also employing a lattice Boltzmann formulation (Roumeas et al 2009;Lucas et al 2017 The present study achieves what we believe are the first simulations of wake bi-modality, capturing both asymmetric states, for a blunt bluff body. No artificial forcing nor inlet perturbations are applied to trigger bi-modality; the flow develops naturally from a steady inlet velocity condition, with bi-modal switches occurring randomly.…”
mentioning
confidence: 66%
“…Simulations which accurately capture the wake unsteadiness at high Reynolds number, and which furthermore extend over the large time scales of bi-modal switching, are very costly. Unsteady simulations of simplified bluff body flows have been performed using partially averaged Navier-Stokes (PANS), simulations (Mirzaei, Krajnović & Basara 2015;Rao et al 2018a), unsteady Reynolds-averaged Navier-Stokes simulations (Khalighi, Chen & Iaccarino 2012), detached eddy simulations and large eddy simulations (Krajnović & Davidson 2003;Serre et al 2013;Aljure et al 2014;Östh et al 2014;Rao et al 2018b), some also employing a lattice Boltzmann formulation (Roumeas et al 2009;Lucas et al 2017 The present study achieves what we believe are the first simulations of wake bi-modality, capturing both asymmetric states, for a blunt bluff body. No artificial forcing nor inlet perturbations are applied to trigger bi-modality; the flow develops naturally from a steady inlet velocity condition, with bi-modal switches occurring randomly.…”
mentioning
confidence: 66%
“…It may be recalled that the height-to-width ratio of the GTS (1.392) is approximately equal to the width-to-height ratio of the squareback Ahmed body (1.35), thus indicating that the aspect ratio of the bluff body is a critical parameter in determining the occurrence of bi-stable flow states (Grandemange et al (2013a), McArthur et al (2016)). While the bi-stable states observed in the wake of squareback Ahmed body occur in the lateral midplane, the two flow states in the GTS wake are observed in the vertical midplane; flow state I in McArthur et al (2016) and Gunes (2010), and flow state II in Schmidt et al (2018), Rao et al (2018b), Ortega et al (2004) and Unaune et al (2005). The wake asymmetry (and the resulting bi-stable flow state) was found to originate at low Reynolds numbers for a squareback Ahmed body, where the flow transitions from a steady asymmetric flow state to an unsteady asymmetric flow state at Re ' 410 via an imperfect supercritical bifurcation (Grandemange et al (2012), Cadot et al (2015)), and is observed at Reynolds numbers well into the turbulent region of flow at Re ' 9:5 Â 10 4 .…”
Section: Introductionmentioning
confidence: 97%
“…The GTS model is representative of a truck and a trailer with no intermediate gap, and is commonly used model in the transportation industry to investigate the aerodynamics of heavy vehicles. While a more detailed description of the near-wake flow topology of heavy vehicles has been presented in Rao et al (2018b), where well-resolved LES were undertaken on a simplified GTS model; a brief description of the literature reviewed is presented here.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations